Combinatorialism revisited - Armstrong, David (Vrin, 2004)
The object of this paper is to argue once again for the combinatorial account of possibility defended in earlier work (Armstrong, 1989, 1997). But there I failed fully to realise the dialectical advantages that accrue once one begins by assuming the hypothesis of logical atomism, the hypothesis that postulates simple particulars and simple universals (properties and relations) at the bottom of the world. Logical atomism is, I incline to think, no better than ‘speculative cosmology’ as opposed to ‘analytic ontology’, to use Donald Williams’ terminology (Williams, 1966, p.74). It is, however, not an implausible hypothesis given the current state of quantum physics. More important for our purposes here, the strictly combinatorial theory that flows rather naturally from the atomist metaphysics shows some promise of continuing to hold (perhaps with a little mutatis mutandis) in a world that is not an atomist world.